2014
DOI: 10.1038/sc.2014.208
|View full text |Cite
|
Sign up to set email alerts
|

The good, the bad and the ugly of catheterization practices among elite athletes with spinal cord injury: a global perspective

Abstract: This study demonstrates that catheter reuse is intimately linked to UTI frequency and provides novel insight on bladder function and management in elite athletes with SCI. Reasons for catheter reuse may be due to a lack of health education and/or a lack of bladder-management resources. (Support: Craig Neilsen Foundation, ICORD, IPC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 25 publications
1
32
0
7
Order By: Relevance
“…Athletes from developing nations were significantly more likely to reuse catheters, and exhibited two times more UTIs per year than athletes from developed nations. The authors suggested that catheter reuse may be due to a lack of resources or a lack of education 9. All athletes utilising intermittent catheterisation should be educated regarding catheter hygiene, including that catheters are for single use only.…”
Section: Uti Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Athletes from developing nations were significantly more likely to reuse catheters, and exhibited two times more UTIs per year than athletes from developed nations. The authors suggested that catheter reuse may be due to a lack of resources or a lack of education 9. All athletes utilising intermittent catheterisation should be educated regarding catheter hygiene, including that catheters are for single use only.…”
Section: Uti Preventionmentioning
confidence: 99%
“…Athletes from developing nations experienced on average 3.5 UTIs per year 9. Furthermore, Derman et al 10 reported a 7.6% frequency of genitourinary illness in Paralympic athletes during the competition period of the London 2012 Paralympic games.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that voiding technique has a major influence on the incidence rates of UTIs. 26 …”
Section: Data Collectionmentioning
confidence: 99%
“…Our sample range in frequency of catheterizing was similar to those from a survey of elite international athletes with SCI (N=61) who catheterized an average of 6 ± 2 times daily; they also reported a range of catheterization 1–10 times/day. 19 …”
Section: Discussionmentioning
confidence: 99%